2013
DOI: 10.1007/s13594-012-0106-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Nucleation and growth rates of lactose as affected by ultrasound in aqueous solutions

Abstract: International audienceThe impact of ultrasound on promoting the crystallisation process including an increase in nucleation rate and the formation of more uniform crystals from a large number of substances has been reported in previous studies. This study aimed to investigate the effectiveness of ultrasound in enhancing the crystallisation process of lactose and to model the effects of ultrasonic variables on nucleation rate, growth rate, and size distribution of lactose crystals in aqueous solutions. Ultrasou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…The sonicated sample at the optimal sonication conditions led to nucleation rates 10.6 times higher and yields 5.6 times higher compared with the control. The results of this study by Zamanipooor et al [116] emphasised the potential effects of ultrasonic treatment in promoting the nucleation rate and yield in the manufacture of lactose without use of solvents. Furthermore, the fact that sonication time had no significant effect Food Eng Rev (P [ 0.05) on the responses implied that sonication duration can be kept to a minimum to save on energy and costs [116].…”
Section: Lactose Crystallisationmentioning
confidence: 82%
See 2 more Smart Citations
“…The sonicated sample at the optimal sonication conditions led to nucleation rates 10.6 times higher and yields 5.6 times higher compared with the control. The results of this study by Zamanipooor et al [116] emphasised the potential effects of ultrasonic treatment in promoting the nucleation rate and yield in the manufacture of lactose without use of solvents. Furthermore, the fact that sonication time had no significant effect Food Eng Rev (P [ 0.05) on the responses implied that sonication duration can be kept to a minimum to save on energy and costs [116].…”
Section: Lactose Crystallisationmentioning
confidence: 82%
“…Although research on sonocrystallisation of lactose has been reported mostly with the use of the anti-solvents, two recent studies by Zamanipooor et al [116] and Dincer et al [41] investigated the effectiveness of ultrasound in enhancing the crystallisation process of lactose in aqueous (i.e., non-solvent) systems. These studies aimed to model the effects of ultrasonic variables on nucleation rate, growth rate and size distribution of lactose crystals.…”
Section: Lactose Crystallisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the crystallization process under ultrasound has been studied by several researchers in recent years (Delgado and Sun ; Zamanipoor and others ), the intrinsic mechanism is still not fully understood. Two widely recognized mechanisms that occur during the propagation of power ultrasound are the cavitation effect and microstreaming.…”
Section: Acoustic Mechanisms Of Power‐ultrasound‐assisted Crystallizamentioning
confidence: 99%
“…The latter plays a significant part in the sugar or food industry, and supersaturated crystallization is the condensation process of the solute from saturated solution. For lactose (Zamanipoor and others ), sucrose (Li and others ), and shortening (Suzuki and others ), supersaturated crystallization can be a practical way of recovery (Kougoulos and others ; Zamanipoor and Mancera ). In general, there are 3 stages in the crystallization process: (1) the supercooled or supersaturated stage; (2) the nucleation stage; and (3) the crystal growth stage (Brito and Giulietti ; Kiani and Sun ).…”
Section: Introductionmentioning
confidence: 99%